Mentoring of Butterfly Pea Flower Processing Business through Brand Rebranding Trade and Game Theory as an Effort to Improve the ASMAN TEMAN SETIA Sawocangkring Economy’s - Cindy Taurusta; Indah Apriliana Sari W; Ika Nur Aieni; Devinatasya Nurtarizka Effendi (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The purpose of this activity focuses on mentoring partners who are a group of processed Telang Flower products in Sawocangkring Village, Sidoarjo. In the previous program, efforts were made to introduce village products through registering business locations on Google Business and Google Maps, as well as registering for Halal Certification. In this increasingly developing digital era, it affects the competitiveness of MSMEs, especially in gaining consumer trust in the products they sell. In this case, partners already have products that are halal certified, but do not yet have a trademark. The problems faced by partners in registering trademarks are that in addition to the lack of understanding of the importance of trademarks, there are several requirements that are difficult to do, for example, creating a logo that will be registered as a trademark. Therefore, this community service program provides mentoring in the field of business management and digital marketing to improve partners' knowledge and skills in managing businesses and marketing products effectively and efficiently. This activity also involves students in off-campus experiences and fulfills lecturers' obligations in community service related to IKU. Thus, this activity can contribute to improving the partner's economy and creating a more sustainable business area.